2002
DOI: 10.1053/euhj.2001.2973
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization of patients with heart failure. A population-based study

Abstract: New cases of heart failure are at high risk of subsequent hospitalization, especially during the first months after diagnosis. Whilst predicting which patients will be hospitalized is difficult, interventions designed to reduce hospitalizations for worsening heart failure should be targeted at elderly inpatients with a new diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
130
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(153 citation statements)
references
References 28 publications
12
130
0
11
Order By: Relevance
“…Just as the study EPICAL and the record OPTIMIZE-HF confirmed the relationship between creatinine and survival, Rassi et al 17 and Cowie et al 20 confirmed the same result, where creatinine was considered an important prognostic factor for survival 17,20,21,25 .…”
Section: Survival Analysissupporting
confidence: 66%
See 1 more Smart Citation
“…Just as the study EPICAL and the record OPTIMIZE-HF confirmed the relationship between creatinine and survival, Rassi et al 17 and Cowie et al 20 confirmed the same result, where creatinine was considered an important prognostic factor for survival 17,20,21,25 .…”
Section: Survival Analysissupporting
confidence: 66%
“…Another variable that was considered a predictor of survival by the multivariate model of survival was age, also present in other studies 19,[22][23][24][25] . For each additional ten years of age, the prognosis was worse, with HR: 1.37 and p < 0.001.…”
Section: Survival Analysismentioning
confidence: 93%
“…The baseline characteristics of the current study are similar to population-based cohorts with regard to age and gender ratio and therefore appear to be representative of the general heart failure population. 14,27,28 In epidemiological studies, the median age for patients with heart failure in the community is approximately 75 years, 14,27,28 similar to the present cohort. Patients were, on average, 10 years younger in the CHARM study; only 19% were aged ≥75 years.…”
Section: Discussionsupporting
confidence: 51%
“…The risk of mortality is particularly high in the early period after diagnosis with approximately 25-30% not surviving six months [1][2][3].…”
Section: Introductionmentioning
confidence: 99%